Antisense peptide nucleic acid–peptide conjugates for functional analyses of genes in Pseudomonas aeruginosa. Issue 22 (15th November 2015) - Maekawa, Kazuhiko; Azuma, Motoki; Okuno, Yousuke; Tsukamoto, Tasuku; Nishiguchi, Kenzo; Setsukinai, Ken-ichi; Maki, Hideki; Numata, Yoshito; Takemoto, Hiroshi; Rokushima, Masatomo
Graphical abstract: Abstract: Pseudomonas aeruginosa is one of the most common and clinically important pathogens because of its resistance to a wide variety of antibiotics. A number of treatments of P. aeruginosa have been developed, but there is still no definitive one. Antisense drugs have a great potential to treat multidrug-resistant P. aeruginosa because this technology, in principle, can inhibit the expression of any essential genes. Nucleic Acid Ther. 2012, 22, 323 reported that peptide nucleic acid (PNA) antisenses conjugated to the carrier peptide (RXR)4 and targeted to ftsZ and acpP (essential genes) had antibacterial activity in P. aeruginosa . However, growth inhibition was also found with peptide–PNA antisense conjugates of mismatched sequences (negative controls), and hence there remains a possibility for considerable enhancement of basal level activity due to the general toxicity. To assess the true potential of peptide–PNA conjugates, we measured sequence-dependent knockdown of the (RXR)4 –PNA conjugates by using a scrambled sequence as a negative control. In addition, we evaluated (RXR)4 –PNA antisenses against three other essential genes ( lepB, lptD and mraY ) and a non-essential gene ( PA1303 ), and confirmed that multiple sequences targeting only the essential genes showed antimicrobial activity in P. aeruginosa PAO1 cells. We also conducted a rescue experiment and confirmed that the antimicrobial activity of anti- mraY antisenses was an on-target effect, not due to general toxicity. These findings indicate that the (RXR)4 –PNA antisense should be a useful tool for target validation of a specific gene and could be a therapeutic platform capable of targeting a variety of genes in P. aeruginosa .